Safe Patient Handling Perceptions and Practices: A Survey of Acute Care Physical Therapists. Issue 5 (1st May 2014) - Olkowski, Brian F.; Stolfi, Angela M.
Abstract : Background: Acute care physical therapists are at risk for developing work-related musculoskeletal disorders (WMSDs) due to manual patient handling. Safe patient handling (SPH) reduces WMSDs caused by manual handling. Objective: The purpose of this study was to describe the patient handling practices of acute care physical therapists and their perceptions regarding SPH. Additionally, this study determined whether an SPH program influences the patient handling practices and perceptions regarding SPH of acute care physical therapists. Methods: Subscribers to the electronic discussion board of American Physical Therapy Association's Acute Care Section were invited to complete a survey questionnaire. Results: The majority of respondents used SPH equipment and practices (91.1%), were confident using SPH equipment and practices (93.8%), agreed that evidence supports the use of SPH equipment and practices (87.0%), and reported the use of SPH equipment and practices is feasible (92.2%). Respondents at a facility with an SPH program were more likely to use SPH equipment and practices, have received training in the use of SPH equipment and practices, agree that the use of SPH equipment and practices is feasible, and feel confident using SPH equipment and practices. Limitations: The study might not reflect the perceptions and practices of the population of acute care physical therapists. Conclusion: Acute care physical therapists are trained to use SPH equipment and practices, use SPH equipment and practices, and have positive perceptions regarding SPH. Acute care physical therapists in a facility with an SPH program are more likely to use SPH equipment and practices, receive training in SPH equipment and practices, and have positive perceptions regarding SPH. Quasi-regulatory organizations should incorporate SPH programs into their evaluative standards.